8th Pieter van Keep Memorial Lecture Estrogen and bone: have we completed a full circle?. (December 2014) - de Villiers, T. J.
Abstract Estrogen therapy was considered first-line therapy for the prevention and treatment of postmenopausal osteoporosis in 1984. Evidence from a large, randomized clinical trial in 2002 proved the efficacy of estrogen in the prevention of all types of osteoporosis-related fractures. Ironically, estrogen was relegated to second-line therapy, based on perceived safety concerns. The historical background to these decisions is presented. It is argued that this decision is not a reasonable reflection of the available evidence, especially in comparison to other available drugs.